Hungary's banking sector: achievements and challenges - Éva Várhegyi (EIB Papers, 2002)
Hungary is generally considered one of the best performing transition countries, having been successful in achieving macroeconomic stabilisation and in creating a market-driven economic system (see, for instance, Fischer and Sahay, 2000; and Weder, 2001). In terms of financial sector reforms, the country is also considered in the advanced league (Bokros, 2001). While we agree to this assessment, it is also true that the degree of monetisation and bank intermediation in the Hungarian economy is surprisingly low, and this despite Hungarys head start in setting a market-driven banking sector. More specifically, in contrast to many other Central and Eastern European Countries (CEECs), Hungary already had a two-tier banking system when the Berlin Wall came down. While the nature of activities that banks could pursue was strictly regulated - limiting competition between banks and resulting in a segmentation of the market - things changed in 1989 when commercial banks - originally confined to corporate customers - were admitted to the retail market. At the same time retail financial institutions were given commercial banking licenses.
Keywords: 330; Bank; Übergangswirtschaft; Bankenreform; Ungarn